N6-Isopentenyladenosine promoted HeLa cell apoptosis through inhibitions of AKT and transforming growth factor β–activated kinase 1 activation - Miao Li; Yonghao Qi; Jing Wei; Lulu Lu; Xuan Zhao; Lijun Zhou (Tumor Biology)
N6-Isopentenyladenosine, a member of the family of plant hormones, possesses anti-cancer activities on a number of cancer cell lines. However, its mode of action in cervical cancer cell remains poorly understood. Our computational docking studies showed that N6-Isopentenyladenosine could bind with the really interesting new gene domain of tumor necrosis factor receptor–associated factor 6, which is an ubiquitination E3 ligase. Tumor necrosis factor receptor–associated factor 6–mediated ubiquitination is known to activate both protein kinase B (also known as AKT) and transforming growth factor β–activated kinase 1, and the really interesting new gene domain comprises the core of the ubiquitin ligase catalytic domain. First, we evaluated the effects of iPA on cervical cancer cell line HeLa using MTT and flow cytometry. Second, we examined the effects of iPA on activation of tumor necrosis factor receptor–associated factor 6–mediated downstream targets using western blot or immunoprecipitation. iPA could reduce HeLa cell proliferation through apoptosis, and such anti-cancer activity is associated with inhibitions of both AKT and transforming growth factor β–activated kinase 1 signaling pathways. In addition, suppression of the anti-apoptotic protein Bcl-2 and elevation of the pro-apoptotic protein Bax were also observed. Anti-proliferation properties of iPA are likely due to its binding at the really interesting new gene domain of tumor necrosis factor receptor–associated factor 6 and loss of AKT and transforming growth factor β–activated kinase 1 activities as a result of functional modulations of tumor necrosis factor receptor–associated factor 6. These results support the emerging notion that tumor necrosis factor receptor–associated factor 6 could serve as a viable target for developing new cancer therapeutics.